2021
DOI: 10.1016/j.esxm.2021.100351
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dysfunction Among Women With Breast Cancer in the Northeastern Part of West Malaysia

Abstract: Introduction Female sexual dysfunction (FSD) is a common complication among breast cancer patients following treatment. Aim To assess the prevalence and factors associated with FSD among breast cancer patients in Kelantan. Methods This cross-sectional study recruited female patients, aged 18–65, who were married and sexually active with their partner, diagnosed with breast cancer, and had undergone breast surgery. Those with underlying psychi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 52 publications
1
18
0
1
Order By: Relevance
“…The present study noted the experience of sexual violence in the reports of participants who highlighted coerced sexual practices, committed without consent, or motivated by fear of their partner. These results show how fundamental it is that health professionals take into consideration the complex interaction between the cultural, relational, and subjective aspects of the sexual experience after breast cancer in order to provide better care in the context of oncological assistance [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present study noted the experience of sexual violence in the reports of participants who highlighted coerced sexual practices, committed without consent, or motivated by fear of their partner. These results show how fundamental it is that health professionals take into consideration the complex interaction between the cultural, relational, and subjective aspects of the sexual experience after breast cancer in order to provide better care in the context of oncological assistance [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Breasts play a significant role in a woman's body image, sexuality, and motherhood [41], and sexuality is one the most impaired domain of quality of life in women with breast cancer [17,42]. There is insufficient research in Croatia that studied sexual quality of life in women with breast cancer and sexual dysfunctions among mentioned women, so the main aim of this study was to determine the relationship between cancer treatment, anxiety and depression with sexual functioning in women with breast cancer and to determine the role of anxiety, depression and coping styles in the development of sexual dysfunctions.…”
Section: Discussionmentioning
confidence: 99%
“…[43]. Cancer is directly linked to the reduction of certain domains in sexual dysfunction, especially in psychological problems such as low desire and arousal, and it can reduce sexual function to a greater degree than problems of organic or functional nature (vaginismus, sexual pain) [41]. Recent research indicates that women with breast cancer report impaired sexual quality of life, and over time, sexual functioning and sexual quality of life become worse [42,44,45].…”
Section: Discussionmentioning
confidence: 99%
“…In Malaysia, a multiethnic, middle-income Asian country with limited supportive cancer care services, open discussions regarding sexual wellbeing between clinicians and patients are scarce due to the sensitive nature of the topic [5][6]. While quantitative studies have reported a high prevalence of sexual dysfunction among Malaysian cancer survivors [7][8], only a handful of qualitative research have examined the sexual health experiences of cancer survivors in the country [6], which tended to be limited to a single cancer site or gender. Understanding the impact of cancer on the sexual wellbeing of patients with different cancers and of both genders is crucial to guide the development of supportive care services that is responsive to the sexual needs of cancer patients in the nation.…”
Section: Introductionmentioning
confidence: 99%